2010
DOI: 10.2478/v10078-010-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Title IX Compliance in NCAA Athletic Departments: Perceptions of Senior Woman Administrators

Abstract: Perceptions of SeniorAchieving gender equity in intercollegiate athletic departments is an on-going challenge that requires constant attention. Although progress has been made since the inception of Title IX in 1972, close attention must always be paid to current inequities and the potential for future inequities of women's athletic programs when compared to men's. The status of gender equity in athletic departments is dynamic, which makes it necessary to consistently interpret Title IX's application to interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Both of these statistics are supported in previous research (Machida-Kosuga, Schaubroeck, & Feltz, 2016;Schneider, Stier, Henry, & Wilding, 2010). Schneider et al (2010) reported 86.4% of the Senior Woman Administrators were white while Machida-Kosuga et al (2016) reported 90.24% of female athletic administrators were white. In addition, the women in the study were well-educated, with 73.2% holding master's degrees.…”
Section: Methodssupporting
confidence: 77%
“…Both of these statistics are supported in previous research (Machida-Kosuga, Schaubroeck, & Feltz, 2016;Schneider, Stier, Henry, & Wilding, 2010). Schneider et al (2010) reported 86.4% of the Senior Woman Administrators were white while Machida-Kosuga et al (2016) reported 90.24% of female athletic administrators were white. In addition, the women in the study were well-educated, with 73.2% holding master's degrees.…”
Section: Methodssupporting
confidence: 77%